2021
DOI: 10.1007/s00423-021-02148-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of liver hypertrophy for extended liver surgery and partial liver transplantation: State of the art of parenchyma augmentation–assisted liver surgery

Abstract: Background Liver surgery and transplantation currently represent the only curative treatment options for primary and secondary hepatic malignancies. Despite the ability of the liver to regenerate after tissue loss, 25–30% future liver remnant is considered the minimum requirement to prevent serious risk for post-hepatectomy liver failure. Purpose The aim of this review is to depict the various interventions for liver parenchyma augmentation–assisting surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 111 publications
(169 reference statements)
0
13
0
3
Order By: Relevance
“…A recent systematic review and meta-analysis on ALPPS and p-ALPPS showed that p-ALPPS is safer than ALPPS in patients without cirrhosis and exhibits the same rate of liver remnant hypertrophy. ALPPS appeared to have better outcomes in cirrhotic patients [ 11 , 12 ]. The best technique is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis on ALPPS and p-ALPPS showed that p-ALPPS is safer than ALPPS in patients without cirrhosis and exhibits the same rate of liver remnant hypertrophy. ALPPS appeared to have better outcomes in cirrhotic patients [ 11 , 12 ]. The best technique is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Restlebervolumen: Entweder wird das Restlebervolumen (RLV) in Prozent des Gesamtlebervolumens („future liver remnant volume to total liver volume percentage“, FLR/TLV) oder in Relation zum Körpergewicht („rest volume to body weight ratio“, RVBWR) angegeben. Bei nicht genügend RLV sind folgende Augmentationsverfahren des RLV möglich: Two-Stage-Hepatectomy, Pfortaderembolisation, Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy (ALPPS) 8 . Grundvoraussetzung für alle Verfahren ist eine vorbestehende regenerative Fähigkeit der Restleber, welche von grundliegender Qualität, Funktion und Durchblutung beeinträchtigt wird.…”
Section: Posthepatektomie-leberversagenunclassified
“…Supported by the vast knowledge acquired throughout the years about liver regeneration and the improvement in surgical techniques, extensive hepatectomies are currently performed in patients with advanced liver cancer. In extreme cases, where surgeons anticipate that the size of the liver after resection will be too small, they have the ability to perform right portal vein embolization or ligation alone among other procedures, in order to promote liver parenchyma augmentation through a hypertrophic mechanism [ 35 ] ( Figure 2 B). These techniques have been developed based on the observation made a century ago, when it was recognized that the occlusion of a segment of the portal vein or the hepatic artery of the rabbit produces hypertrophy in the contralateral lobe while atrophy occurs in the side of occlusion [ 36 ].…”
Section: Interdisciplinary Models Applied To Translational Medicinementioning
confidence: 99%
“…These techniques have been developed based on the observation made a century ago, when it was recognized that the occlusion of a segment of the portal vein or the hepatic artery of the rabbit produces hypertrophy in the contralateral lobe while atrophy occurs in the side of occlusion [ 36 ]. Together, portal and hepatic vein embolization induce faster growth of the contralateral liver than portal vein embolization alone [ 35 ].…”
Section: Interdisciplinary Models Applied To Translational Medicinementioning
confidence: 99%